South Asia Conundrum The Great Power Gambit - Jain, B. M. (Lexington Books, 2019)
This book forensically examines geopolitical, geo-economic, and geostrategic, implications of the interventionist role of extra-regional powers in South Asia and its extended neighborhood, Afghanistan and Central Asia in particular.